Influência do ensino remoto emergencial na atuação de docentes universitários na área de atividade física adaptada - Rossi-Andrion, Patricia (2022)
Among the various consequences resulting from the pandemic triggered by Covid-19 in 2020, it was the interferences in the educational scenario that it was stand out. Significant changes in the university academic routine led to the need to reorganize teaching for the non-presential modality, resorting to remote activities aimed to training teachers in the most different areas of knowledge. Particularly in the Adapted Physical Activity (APA) area, the importance and the needs to understand the resources in teaching strategies that it has been used by teachers of Higher Education Institutions (HEIs) are highlighted, witch teach the subjects related about this theme, which was oriented to the formation of the teachers to act in the inclusion of the Target Public of Special Education (TPSE). Thus, this study aimed to analyze the resources and teaching strategies developed by university professors to the pre-service of teachers in Adapted Physical Activity during the Emergency Remote Teaching (ERT), due to the pandemic resulting from the Covid-19. Specifically, it was intended to: a) characterize the profile of Adapted Physical Activity teachers who worked during the ERT; b) identify which resources and teaching strategies have been developed for teacher training in APA during the ERT; c) describe how the resources and teaching strategies were operationalized by the professors; d) identify the support structure provided by the HEIs according the ERT; e) analyze the consequences of the ERT in the teachers training in APA from the perspective of the HEIs’ professors. In the first stage of the study, the sample consisted of 32 professors from public and private HEIs who taught the APA subjects (or equivalent titles) during the ERT, by a questionnaire which was sent by email (Google Forms) with the purpose to identifying accurate information and screening participants selected and invited to be interviewed. In the second stage, a structured interview was carried out with 11 professors from HEIs in the five Brazilian regions. The interviewers took place via Google Meet and lasted an average of one an half hour, in order to understand how teaching strategies in APA were occurred during the ERT. Data treatment was based on thematic analysis. Three thematic categories were identified: a) structuring, reorganization and adaptation of HEIs to the ERT (contextualization; actions; time; period; assistance of HEIs); b) challenges of the ERT for initial professional training in APA (teaching strategies; evaluation criteria; possibilities and limits); and c) consequences of ERT (return to the face-to-face model; teaching performance; student performance). The effectiveness and need for the insertion of the ERT during the pandemic was observed so that academic activities remained active. It was necessary for the professors to reorganize their disciplines, as well as modify the teaching strategies and make the evaluation criteria more flexible. There was a great overload of work, interfering with the physical and emotional aspects of the professors, in addition to the great concern of accessibility and permanence of the students regarding the technological devices. With regard to initial professional training in APA, it was possible to highlight the need for practical experiences and face-to-face personal interaction. But overall, the ERT was positive and managed to achieve in objectives in the situation in which it was inserted.